2019
DOI: 10.1038/s41598-019-55240-5
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-based screening identifies molecules targeting the substrate-binding ankyrin repeat domains of tankyrase

Abstract: The PARP enzyme and scaffolding protein tankyrase (TNKS, TNKS2) uses its ankyrin repeat clusters (ARCs) to bind a wide range of proteins and thereby controls diverse cellular functions. A number of these are implicated in cancer-relevant processes, including Wnt/β-catenin signalling, Hippo signalling and telomere maintenance. The ARCs recognise a conserved tankyrase-binding peptide motif (TBM). All currently available tankyrase inhibitors target the catalytic domain and inhibit tankyrase’s poly(ADP-ribosyl)ati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 81 publications
(125 reference statements)
0
26
0
Order By: Relevance
“…While the development of TNKS inhibitors mainly focussed on the inhibition of the catalytic domain, the function of tankyrases is coupled to many regulatory processes beyond its catalytic function 3 , 23 , 25 . With newer findings about the scaffolding function of tankyrases and its contribution to the regulation of the catalytic activity, several reports have suggested that the inhibition of multimerization or protein-binding function may represent an effective way for the specific inhibition of tankyrases 23 , 34 36 , 43 . Such inhibitors would also be valuable chemical probes aiding the investigation of TNKS mechanism of function in the cell.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While the development of TNKS inhibitors mainly focussed on the inhibition of the catalytic domain, the function of tankyrases is coupled to many regulatory processes beyond its catalytic function 3 , 23 , 25 . With newer findings about the scaffolding function of tankyrases and its contribution to the regulation of the catalytic activity, several reports have suggested that the inhibition of multimerization or protein-binding function may represent an effective way for the specific inhibition of tankyrases 23 , 34 36 , 43 . Such inhibitors would also be valuable chemical probes aiding the investigation of TNKS mechanism of function in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, the assay will help to identify small chemical inhibitors of TNKS ARC-protein binders and SAM-SAM-interactions. With only a few reported small chemical binders for TNKS ARCs to date 34 36 , we could already expand the number with our validatory screening efforts appreciably. Last, X-ray crystallographic studies of ARCs with these molecules would provide important insights into the binding modes and could lead to a structure guided design of novel chemical probes with higher affinity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Often but not exclusively, tankyrase-mediated PARylation is recognized and ubiquitinated by the E3 ligase RNFL146 (Zhang et al, 2011), this targets substrates for proteasomal degradation and thus regulation is commonly via alteration of protein stability. However, evidence is also emerging that tankyrases can have catalytic independent functions (Pollock et al, 2019). As tankyrase biology is relatively less well understood than that of PARP1-3, it is likely that further, unknown tankyrase functions exist.…”
Section: The Tankyrases -Parp 5a and 5bmentioning
confidence: 99%